Islam, Muslims, and the Coloniality of Being: Reframing the Debate on Race and Religion in Modernity - Abbasi, Iskander (Journal for the study of religion, 2020)
This article aims to more thoroughly intersect the figure of the Muslim into the framework of the coloniality of being, and into the narrative of race and religion in modernity. Two areas of concern are investigated: First, how Islamophobia aided in forming the coloniality of being in ways that decolo-nial scholarship - namely that of leading Latin American decolonial thinker, Nelson Maldonado-Torres - is seemingly unaware of or downplays, and second, how a rereading of a number of the key events and figures that define a decolonial discourse on race and religion, such as the Valladolid debates (1550-1551) and the figure of Christopher Columbus, help to more rigorously conceptualize the figure of the Muslim in relation to the coloniality of being.